Pattern of Gross Congenital Anomalies in The Biggest Maternity Hospital of Pakistan - ., MUHAMMAD SAEED (Journal of Fatima Jinnah Medical University, 2018)
This study was a descriptive case series on “Pattern of gross congenital anomalies in the biggest maternity hospital of Pakistan.” The objective was to identify the pattern of gross congenital anomalies in newborns at the tertiary care hospital and to enlist the preventable predisposing risk factors leading to such anomalies. The study period was three years with effect from 01-07-2007 to 01-07-2010. It was conducted in Lady Willingdon hospital Lahore. A proforma was devised to collect data There were thirty five thousand six hundred and six (35604) deliveries in our study period and six hundred (600) newborns had various gross congenital anomalies. Mean age of the parturient was 25.21±4.63years. 63 % were multi gravid whereas 37 % were primi gravid. Mean gestational age was 30.20±5.95 weeks. Neural tube defects were the commonest congenital anomalies either alone or in combination with other anomalies; accounting for a total 63.0% (378 newborns). It was found that 1out of 59.39 newborns had gross congenital anomalies making the prevalence of 16.85 per 1000 births. The commonest associated risk factor was cousin marriage. Congenital anomalies are a distressing condition not only for the parents but also for health care providers. Public awareness about such hazards of cousin marriage can reduce the prevalence. Neural tube defects can be reduced by pre conception folic acid & multivitamin therapy. An early prenatal diagnosis and termination of pregnancy can help in alleviating psychological distress related to late diagnosis and consequently late termination of pregnancy. It was concluded that the neural tube defects were the most common congenital anomalies and the most common associated risk factor was cousin marriage.